Self-consistent growth of single-crystalline (2̄01)β-Ga2O3 nanowires using a flexible GaN seed nanocrystal. Issue 4 (11th January 2017) - Song, Pengyu; Wu, Zhengyuan; Shen, Xiyang; Kang, Junyong; Fang, Zhilai; Zhang, Tong-Yi
Abstract : Single-crystalline (2̄01)β-Ga2 O3 nanowires were grown by using a flexible GaN seed nanocrystal "self-organizing" around catalytic Pt droplets. Abstract : Single-crystalline (2̄01)β-Ga2 O3 nanowires were grown by using a flexible GaN seed nanocrystal "self-organizing" around catalytic Pt droplets. The atomic structures of β-Ga2 O3 (2̄01) epitaxy on GaN(0001) were investigated by X-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, Raman spectroscopy, and cathodoluminescence (CL). The synthesized nanowires prepared by self-consistent growth are single crystals of pure β-Ga2 O3 phase with (2̄01)-orientation and high crystalline quality and have intense ultraviolet–blue CL emission properties at room temperature.